Diagnostic and therapeutic pathways for lymphoma patients: expert consensus through Nominal Group Technique and Delphi methodology - Guarini, Attilio; Bozzoli, Valentina; Ciavarella, Sabino; Cimminiello, Michele; Donatelli, Francesca; Fama, Angelo; Fesce, Vincenza Fernanda; Fraticelli, Vincenzo; Gaudio, Francesco; Greco, Giuseppina; Martellini, Augusto; Merchionne, Francesca; et al. (Frontiers in Oncology, 2025)
IntroductionLymphomas encompass a heterogeneous group of B- and T-cell malignancies necessitating a complex and precise management. With the aim to define standardized diagnostic and therapeutic pathways across multiple hematology centers in Italy, the “Right Path 4 Lymphomas” project was designed as a multidisciplinary expert platform designed to establish consensus-driven diagnostic and therapeutic pathways.MethodsUsing a two-phase methodology – the Nominal Group Technique followed by a Delphi process – experts systematically evaluated and prioritized key diagnostic and therapeutic topics for five major lymphoma subtypes: classical Hodgkin lymphoma, diffuse large B-cell lymphoma, follicular lymphoma, mantle cell lymphoma, and peripheral T-cell lymphomas.ResultsThe Delphi process achieved a high level of consensus on 264 of 270 statements (97.8%), reinforcing the importance of multidisciplinary collaboration in shaping evidence-based recommendations. Key areas of agreement included histopathologic and molecular diagnostic standards, risk-adapted treatment approaches integrating novel immunotherapies, and structured follow-up strategies. However, areas of debate remained over the clinical utility of minimal residual disease monitoring, optimal sequencing of immunotherapies, and the potential of CAR-T therapy versus bispecific antibodies.DiscussionThis project highlights the need for a structured, consensus-driven approach to lymphoma care that aligns with evolving international guidelines while addressing the distinct regulatory and healthcare landscape in Italy. The findings provide a valuable framework for clinicians and policymakers to optimize lymphoma management, balancing innovation with the allocation of resources and clinical feasibility.